Effect of Metal Ions, Chemical Agents, and Organic Solvent on Bacillus Sp.R2 Chitinase Activity. (2016) - Cheba, Ben Amar; Zaghloul, Taha Ibrahim; EL-Massry, Mohamad Hisham; EL-Mahdy, Ahmad Rafik
Abstract: Bacillus sp . R2 purified chitinase was subjected to the effect of metal ions, chemical agents, and organic solvent on its activity, the results showed that K +, Mn 2+, Na +, Mg 2+ and Ca 2+ stimulated chitinase activity by 2, 4, 7, 15 and 21% respectively whereas Cu 2+, Fe 2+, Zn 2+, Ag + and Hg 2+ inhibited the enzyme. 10 mM β-mercaptoethanol and EDTA decreased the activity by 38.7 and 78.4% respectively whereas 1% SDS inactivated the enzyme completely, also 1 mM galactose, glucose and N-acetyl glucosamine inactivated the enzyme by about 14.4, 25.2 and 38.7% respectively ethanol, acetone and isopropanol inhibited about 30% of chitinase activity however full or nearly full inhibition was observed with chloroform diethylether and ethylacetate. Furthermore the chitinase shelf life was 30 day at -20C and survived 4 freezing and thawing with lost of about 30% of its original activity. This is the first contribution about marine chitinase characterization study from novel gram variable Bacillus isolated from the Red sea.